Recent Development on Treatment of Crude Oil Contaminated Water Using Agricultural Waste – A Review - Akinyemi O. P. (International Journal of Engineering and Management Research, 2020)
Crude oil recovery processes generate large volumes of crude oil-contaminated water. Crude oil-contaminated water was noted to contain hydrocarbons (including saturates and aromatics) as well as non-hydrocarbons. Some hydrocarbons in the contaminated water are found to be carcinogenic, neurotoxic, and genotoxic to humans and other organisms. Thus, the exposure of human being and other organism like fishes in the marine environment to these hydrocarbons through skin contact to such contaminated water or consumption of contaminated food and water may be very dangerous. The remediation of such oil contaminated water has become a crucial problem in oil producing countries and requires more drastic attention. Several technologies have been deployed at solving this problem. Utilization of agricultural wastes as adsorbents has however, been found to be more attractive to researches due to its environmental friendly tendencies and economic viability. This paper reviewed the attempt of researchers at addressing this problem by using agricultural wastes like banana peel, rice husk, etc as sorbent for removal of the oil from the crude oil-contaminated water. It was observed that agricultural wastes compete favourably with synthetic adsorbents in oil removal from crude oil contaminated water. Though many agricultural products have been investigated, there are some like plantain peel, papaya peel and water melon rind that need to be considered for this treatment.